Adsorption of [AuCl4]– on Ultrasonically and Mechanical-Stirring Assisted Mg/Al-NO3 Hydrotalcite-Magnetite - Triastuti Sulistyaningsih; Sri Juari Santosa; Dwi Siswanta; Bambang Rusdiarso (Universitas Gadjah Mada, 2016)
It has been examined the application of Mg/Al-NO3 hydrotalcite-magnetite synthesized mechanically (MHT) and ultrasonically (UMHT) by co-precipitation method as adsorbents for [AuCl4]– from aqueous solution. Two techniques of synthesis were conducted to determine the effect on the increase of adsorption ability of the [AuCl4]–. Magnetite and Mg/Al-NO3 hydrotalcite-magnetite synthesized by co-precipitation with modifications hydrothermal treatment at 120 °C for 5 h. The adsorbents were characterized by Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) and Vibrating sample magnetometer (VSM). Adsorption studies were done by getting the optimum pH, optimum contact time and the optimum concentration. A result of the adsorption study of [AuCl4]– on both adsorbents was optimum at pH 3 and fitted well to Langmuir isotherm and pseudo second-order kinetic models. The adsorption capacity of UMHT (ultrasonic technique) was 66.67 mg g-1 and it was higher than that of MHT (mechanic technique), i.e. 31.25 mg g-1. This shows that the ultrasonic radiation technique can increase the adsorption capacity of the [AuCl4]–. Based on the desorption using 0.5 mol L-1 NaOH solution, more [AuCl4]– was eluted from MHT, indicating that [AuCl4]– was weakly bound on MHT than UMHT.